2019
DOI: 10.1155/2019/5028181
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione “Redox Homeostasis” and Its Relation to Cardiovascular Disease

Abstract: More people die from cardiovascular diseases (CVD) than from any other cause. Cardiovascular complications are thought to arise from enhanced levels of free radicals causing impaired “redox homeostasis,” which represents the interplay between oxidative stress (OS) and reductive stress (RS). In this review, we compile several experimental research findings that show sustained shifts towards OS will alter the homeostatic redox mechanism to cause cardiovascular complications, as well as findings that show a prolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(84 citation statements)
references
References 127 publications
(178 reference statements)
2
76
0
Order By: Relevance
“…In addition, low PON1 levels in human plasma are associated with increased risks of heart disease (Schrader and Rimbach 2011;Wang et al 2012;Litvinov, Mahini, and Garelnabi 2012). GSH, the most abundant antioxidant in the heart, protects against oxidative stress, myocardial infarction and coronary artery disease at physiological levels (Bajic et al 2019).…”
Section: Betanin Atherogenesis and Cardiovascular Diseasesmentioning
confidence: 99%
“…In addition, low PON1 levels in human plasma are associated with increased risks of heart disease (Schrader and Rimbach 2011;Wang et al 2012;Litvinov, Mahini, and Garelnabi 2012). GSH, the most abundant antioxidant in the heart, protects against oxidative stress, myocardial infarction and coronary artery disease at physiological levels (Bajic et al 2019).…”
Section: Betanin Atherogenesis and Cardiovascular Diseasesmentioning
confidence: 99%
“…GSH is the principal intracellular antioxidant, which may act directly by scavenging reactive oxygen and nitrogen species and plays an essential role in several metabolic and cellular processes. Deficiency of GSH causes cellular risk for oxidative damage, and thus, as expected, GSH imbalance is observed in a wide range of pathological conditions including cardiometabolic and cardiovascular diseases, tuberculosis, HIV, diabetes, neurodegenerative diseases, infertility, and cancer [70][71][72][73]. Although it is widely accepted that the GSH antioxidant defenses of the body decrease linearly with age [74], studies on old rats that had never been sick before revealed GSH was at the same level as in young rats [29].…”
Section: Glutathionementioning
confidence: 55%
“…Although intracellular GSH mainly exists as a monomer in reduced form (more than 98% of GSH), severe oxidative stress (OS) can overcome the ability of the cell to reduce GSSG to GSH leading to accumulation of GSSG [69]. Thus, the ratio of GSH and GSSG is considered to be a marker of OS [70].…”
Section: Glutathionementioning
confidence: 99%
“…Indeed, it is well know that free radical play a crucial role in the pathogenesis of several disease including pulmonary, cancer, rheumatoid, diabetes, cardiovascular diseases, atherosclerosis, hypertension, ischemia/reperfusion injury, etc [16][17][18][19][20] . Thus, the present study evaluate the LAMIC antioxidant activity by using three methods that are DPPH radical scavenging activity assay, ABTS radical cation scavenging activity assay and the FRAP assay.…”
Section: Discussionmentioning
confidence: 99%